Rediscovered and new perisphaerine cockroaches from SW China with a review of subfamilial diagnosis (Blattodea: Blaberidae) - Li, Xin-Ran; Wang, Li-Li; Wang, Zong-Qing (Zootaxa, 2018)
The taxonomic records of Chinese perisphaerine cockroaches were scattered in literature, and therefore a dedicated study is desired to update our knowledge. This paper reviews the subfamilial diagnosis and Chinese species, mostly from southwestern China. We provide high-definition habitus photos and drawings, the latter emphasizes the genitalia of both sexes, which are generalized with diagrams, abstracted from specimens examined. A total of 18 species are recorded in four genera, including Perisphaerus, or pill cockroach, the type genus of the subfamily. Two new genera and three new species are proposed: Achatiblatta achates gen. & sp. nov., Frumentiforma frumentiformis gen. & sp. nov., and Pseudoglomeris montana sp. nov.. Pseudoglomeris has five new junior synonyms: Corydidarum, Trichoblatta, Kurokia, Glomerexis, and Glomeriblatta; the following combinations are thus revived or new: Ps. aerea comb. nov., Ps. angustifolia comb. nov., Ps. beybienkoi comb. nov., Ps. fallax comb. nov., Ps. magnifica comb. rev., Ps. montshadskii comb. nov., Ps. nigra comb. nov., Ps. sculpta comb. nov., Ps. semisulcata comb. rev., Ps. tibetana comb. nov., and Ps. valida moderata comb. nov.. The following species are revalidated and combinations revived: Pe. pygmaeus comb. rev., Ps. dubia comb. & sp. rev., and Ps. planiuscla comb. & sp. rev.